What Italian Defense Attorneys Know about Factors Affecting Eyewitness Accuracy: A Comparison with U.S. and Norwegian Samples - Magnussen, Svein; Safer, Martin A.; Sartori, Giuseppe; Wise, Richard A. (Frontiers in Psychiatry, 2013)
We surveyed 100 Italian defense attorneys about their knowledge and beliefs about factors affecting eyewitness accuracy. The results of a series of similar surveys show that U.S. defense attorneys outperformed other legal professions, including U.S. prosecutors and U.S. and European judges. The present results for the Italian defense attorneys indicate a similar trend. However, analyses of the results suggest that the defense attorney’s’ superior performance on the eyewitness statements was, in part, a product of their skepticism about the accuracy of eyewitness testimony rather than their greater knowledge.